Evaluation of n-(n-butyl) thiophosphoric triamide- treated urea with and without chicken manure on growth, yield and postharvest quality of sweet potato [Ipomoea batatas (L.) Lam.] - Mohd Nasirudin, Muhammad Zulhilmi (2020)
Sweet potato is a versatile crop that has a high output of yield and biomass, however, it is decreased in demand through the inefficiency of nitrogen management. Farmers are unable to control N losses through water sliding, nitrification, denitrification, volatilization, mineralization and immobilization. Due to N losses, farmers are unaffordable to increase input cost caused by the demand for chemical and organic fertilizer which increases over the years, and low nutrient available in soil may affect crop production and market value. However, most of farmers use excess usage of urea in order to replace the amount of N losses which can achieve the maximum productivity with optimum dosage. Thus, the use of urease inhibitor in fertilizer can reduce nitrogen losses by inhibiting the hydrolytic activity of urea decomposition. N(n-butyl) thiophosporic triamide (NBPT) to improve nitrogen availability in the soil while reducing N loss, especially in tropical conditions. The objectives of the study were i) to investigate the effects of NCU on the plant growth, plant physiology, N content and yield of sweet potato, ii) to determine the effects of NCU and NIU on the plant growth, plant physiology, N content and yield of sweet potato, iii) to identify and differentiate the effect on postharvest quality of sweet potato (Ipomoea batatas) under ambient and cold storage. Experiment 1 was arranged in RCBD while in experiment 2 was arranged in CRD. Both experiment was conducted in Field 15, Faculty of Agriculture, University Putra Malaysia, Serdang, Selangor. Anggun 2 was the variety of cutting sweet potato purchased from commercial farmers in Banting. A standard cutting (25-35 cm) was treated with carboryl or malathion to avoid disease infection under the shaded area. Experiment 1 (1A and 1B), has a total of 12 treatments subjected to two factors, with (T1-T6) and without chicken manure (CM) (T7-T12). All the treatments used was labeled as [T1] Farmer practices (96 kg N/ha) + CM, [T2] 0 kg N/ha of NCU + CM, [T3] 57.6 kg N/ha of NCU + CM, [T4] 76.8 kg N/ha of NCU + CM, [T5] 96 kg N/ha of NCU + CM, [T6] 115.2 kg N/ha of NCU + CM, [T7] Farmer practices (96 kg N/ha), [T8] 0 kg N/ha of NCU, [T9] 57.6 kg N/ha of NCU, [T10] 76.8 kg N/ha of NCU, [T11] 96 kg N/ha of NCU, and [T12] 115.2 kg N/ha of NCU. Experiment 2 (2a & 2b) has a total of seven (7) treatments with proposed 3 new treatments (T5-T7) and labeled as [T1] Farmer practices (120 kg N/ha urea), [T2] 72 kg N/ha of NCU, [T3] 96 kg N/ha of NCU, [T4] 120 kg N/ha of NCU, [T5] 72 kg N/ha of NIU, [T6] 96 kg N/ha of NIU and [T7] 120 kg N/ha of NIU. In conclusion, Experiment 1, NCU treated with CM show significant effect and better result in yield than NCU treated without CM by 30.99%. Plant treated with 76.8 kg N/ha urea NCU showed the highest and recommend to the farmers either with or without CM to maximize the plant growth (shoot fresh and dry weight; tuber fresh and dry weight) yield of sweet potato and nutrient uptake of sweet potato. While, in Experiment 2, NIU showed a better performance in ammonium content by 34.98% of urease hydrolysis activity better than NCU while 96 kg N/ha is the consistent rate to showed the highest significant in tuber fresh weight by 18.49% and 20.41% of NCU and NIU respectively as compared to control. In both experiments 1B and 2B, cold storage showed a significant effect in controlling postharvest quality in terms of shelf-life better than ambient storage (normal practices). As a recommendation, farmers are advised to use fertilizer with urease inhibitors to maximize crop production.